Frequency of application of 24-epibrassinolide on plant growth, physiology and postharvest fruit quality of Cantaloupe grown at elevated temperature - Amarasinghe, Rathnayake Mudiyanselage Nilusha Thushari; Sakimin, Siti Zaharah; Megat Wahab, Puteri Edaroyati; Ramlee, Shairul Izan; Nakasha, Jaafar Juju (Taylor and Francis, 2023)
Reduction of yield in tropical greenhouses is an issue with Cucumis melo L. var. cantaloupensis. A natural occurring hormone, 24-epibrassinolide (EBR), regulates cellular activities and physiological processes of plants and signaling. To determine effects of EBR application, cantaloupe cvs. Himalai-99 and Glamour (factor 1) were treated with 0.1 mg∙L−1 EBR applied over four frequencies (factor 2) as; F1: no EBR (control), F2: at 15 DAT (days after transplant), F3: at 15 + 30 DAT, and F4: at 15 + 30 + 45 DAT at 47 ± 3°C (5°C higher than the ambient greenhouse) in a factorial Randomized Complete Block Design (RCBD) with four replicates. Postharvest fruit quality was monitored at room temperature (26°C) in a completely randomized design with four replicates. Data were analyzed using Analysis of Variance, mean separation with least significant difference and associations between parameters with Pearson correlation. Application of EBR at 15 + 30 DAT (F3) increased plant dry weight, leaf area, specific leaf area, root length, root surface area, photosynthesis rate, stomatal conductance, transpiration rate and chlorophyll content. It increased the quantum efficiency of photosystem II, peroxidase and catalase activities by 50%, stomatal length and width by 75% and decreased malondialdehyde and proline content by 56%. Pre-harvest foliar application of EBR at 15 + 30 DAT reduced postharvest weight loss and ethylene emission rate by two fold and reduced ascorbic acid and antioxidant depletion rates during storage. The EBR application at 15 + 30 DAT produced the best plant and fruit quality performances, while the application of EBR at fruit development stage (45 DAT) caused reduced fruit quality.